COFFEE CHERRIES DRYING PROCESS AND THE INFLUENCE OF ENVIRONMENT RELATIVE HUMIDITY IN THE MATHEMATICAL MODELING, MOISTURE CONTENT, AND ENTHALPY OF VAPORIZATION - Coradi, Paulo Carteri; Borém, Flávio Meira; Reinato, Carlos Henrique (ENERGIA NA AGRICULTURA, 2014)
The drying operation is one of the most important stages of the coffee production. Thus, we aimed to evaluate the influence of the ambient relative humidity (40, 50 and 60%) in the natural process of coffee (Coffea Arabica L.) drying at different air temperatures (23 °C, 40 °C and 60 °C) using mathematical modeling, equilibrium moisture content, and enthalpy of vaporization. Coffee cherries natural processed and dried with a drier of fixed layer was used. The study was conducted at the Department of Engineering and Technology Center of Post-Harvest Café, of the Federal University of Lavras. The results showed that the equilibrium water content of the coffee cherry is directly proportional to the water activity, and decreased increasing temperature during the same water activity. The Oswin model showed the best fit to describe the phenomenon of hygroscopicity of the coffee cherry. The latent heat of desorption increased decreasing the water content and decreased increasing temperatures of the same water content. In addition, the Midilli model showed the best fit to the drying data. Furthermore, the Gibbs free energy increased increasing temperature, it’s their magnitude being was positive in the temperature range used in this study. In conclusion, the different ambient relative humidities did not significantly influenced the processes of drying coffee cherries. KEYWORDS: quality, dimensioning, project, dryer. SECAGEM DE CAFÉ CEREJA E A INFLUÊNCIA DA UMIDADE RELATIVA DO AR AMBIENTE NA MODELAGEM MATEMÁTICA, EQUILÍBRIO HIGROSCÓPICO E NA ENTALPIA DE VAPORIZAÇÃO RESUMO: A secagem é uma das etapas mais importantes no processamento de café. Assim, o objetivo foi avaliar a influência da umidade relativa do ar ambiente (40, 50 e 60%) na secagem do café natural (Coffea arábica L.) em diferentes temperaturas (23 °C, 40 °C e 60 °C) com modelagem matemática, o equilíbrio higroscópico e a entalpia de vaporização. O trabalho foi realizado no Departamento de Engenharia e Centro de Tecnologia de Pós-Colheita Café, Universidade Federal de Lavras. No experimento foi utilizado café cereja, processamento de forma natural e seco em camada fixa. Nos resultados obtidos observou-se que o teor de água de equilíbrio do café cereja é diretamente proporcional à atividade da água e diminui com o aumento da temperatura, para uma mesma atividade de água. O modelo de Oswin apresentou-se melhor para o ajuste e descrição do fenômeno de higroscopicidade o café cereja. O calor latente de dessorção aumentou com a diminuição do teor de água e diminui com o aumento da temperatura, para o mesmo conteúdo de água. O modelo de Midilli foi o melhor, para o ajuste dos dados experimentais de secagem. Além disso, a energia livre de Gibbs aumentou com o aumento da temperatura, sendo as suas grandezas positivas na gama de temperatura utilizada neste estudo. Em conclusão, as diferentes umidades relativas do ar ambiente não influenciaram significativamente nos processos de secagem do café. PALAVRAS-CHAVE: qualidade, dimensionamento, projeto, secador.